Processing of fecal sludge to fertilizer pellets using a low-cost technology in Ghana - Nikiema, Josiane; Cofie, Olufunke O.; Impraim, Robert; Adamtey, Noah (Canadian Center of Science and Education, 2013)
This paper describes a study that was aimed at optimizing the pelletization of fecal sludge-based fertilizers for agricultural use. The process developed is easy to implement and increases the marketability of the products while also addressing a serious health and environmental challenge. The study took place during the period 2011-2012 in Ghana. The fecal sludge, rich in nutrients and organic matter, was dried and used to produce five different fertilizers (i.e., four formulations of compost and one with gamma irradiated material). Each material was then pelletized using locally constructed machinery. Key operating parameters, such as moisture content (10-55% in mass), binder type (clay or starch) and concentration (0-10% in mass), were varied and their impacts on the characteristics of pellets (e.g., amount of fine materials generated, length distribution or stability of pellets, and pellet disintegration rate) were also followed. Given the low analyzing capabilities of developing countries, some simple analytical methods were developed and used to compare pellets produced under different conditions. The results confirmed that the addition of 3% of pregelatinized starch is recommended during pelletization of fecal sludge-based fertilizers. Applicable moisture contents were also identified per fertilizer type, and were found to comprise between 21 and 43%.